Pesan-Pesan Toleransi Beragama Dalam Konten Youtube Gita Savitri Devi (Al-Adyan: Journal of Religious Studies, 2021)
The use of social media to transform positive values among the younger generation and millennials, including the values of religious tolerance, is very significant to do in the current era of information technology. Relevant to that, this study aims to explore messages of religious tolerance found on social media, in this case the vlog belongs to Gita Savitri Devi, a youtuber and social media activist. This research is a qualitative type of library research, because the data collected is obtained from library materials, especially video documentation from Gita's YouTube. The data were analyzed using content analysis techniques. The results obtained are that in Gita Safitri Devi's vlog, especially the seven video shows, there are five elements of religious tolerance including, acknowledging the rights of others, respecting other people's beliefs, agreeing in disagreement, understanding each other, as well as awareness and honesty. It can be concluded that Gita Savitri Devi through her vlog seeks to participate in transforming the values of religious tolerance to young people, especially millennials who love social media.Pemanfaatan media sosial untuk mentransformasikan nilai-nilai positif di kalangan generasi muda dan kaum milenial, termasuk nilai-nilai toleransi beragama, sangat signifikan untuk dilakukan pada era teknologi informasi saat ini. Relevan dengan itu, penelitian ini bertujuan untuk menggali pesan-pesan toleransi beragama yang terdapat di media sosial, dalam hal ini vlog miliki Gita Savitri Devi, seorang youtuber dan penggiat media sosial. Penelitian ini termasuk kualitatif dengan jenis library research, karena data-data yang dikumpulkan diperoleh dari bahan-bahan pustaka khususnya dokumentasi video yang berasal dari youtube milik Gita. Data dianalisis menggunakan teknik analisis isi. Hasil yang diperoleh adalah bahwa dalam vlog Gita Safitri Devi khususnya pada tujuh tayangan video, terkandung lima unsur toleransi beragama meliputi, mengakui hak orang lain, menghormati keyakinan orang lain, agree in disagreement, saling mengerti, serta kesadaran dan kejujuran. Dapat disimpulkan bahwa Gita Savitri Devi melalui vlog-nya berupaya untuk ikut mentransformasikan nilai-nilai toleransi beragama kepada kalangan muda, terutama kaum millenial yang menggandrungi media sosial.